2014
DOI: 10.1016/j.immuni.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Activated T Cells Secrete an Alternatively Spliced Form of Common γ-Chain that Inhibits Cytokine Signaling and Exacerbates Inflammation

Abstract: SUMMARY The common γ-chain (γc) plays a central role in signaling by IL-2 and other γc–dependent cytokines. Here we report that activated T cells produce an alternatively spliced form of γc mRNA that results in protein expression and secretion of the γc extracellular domain. The soluble form of γc (sγc) is present in serum and directly binds to IL-2Rβ and IL-7Rα proteins on T cells to inhibit cytokine signaling and promote inflammation. Sγc suppressed IL-7 signaling to impair naïve T cell survival during homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 49 publications
10
102
0
1
Order By: Relevance
“…CSE significantly reduced the total number of LN cells ( Figure 1B), and we also observed that the numbers of naïve (CD44 Figure 1C), since the number of overall LN cells was decreased ( Figure 1B). Since sγc production is enhanced in activated T cells, 22 these data indicate that a reduction in the sγc level by CSE results from a diminished cell number, specifically activated T cells.…”
Section: Cse Reduces Sγc Expressionmentioning
confidence: 74%
See 1 more Smart Citation
“…CSE significantly reduced the total number of LN cells ( Figure 1B), and we also observed that the numbers of naïve (CD44 Figure 1C), since the number of overall LN cells was decreased ( Figure 1B). Since sγc production is enhanced in activated T cells, 22 these data indicate that a reduction in the sγc level by CSE results from a diminished cell number, specifically activated T cells.…”
Section: Cse Reduces Sγc Expressionmentioning
confidence: 74%
“…IL-2, which plays a critical role in the development and homeostasis of Treg cells, 39 is elevated in COPD patients who show disease stability, 40 inducing dominant upregulation of Treg cells in smokers with preserved lung function compared with COPD patients. 41 As our previous studies demonstrated that sγc inhibits IL-2 signaling, 22 excessive T cell response with IL-2-induced Treg cells. On the other hand, Treg development depends on IL-2 and TGFβ, which is also linked to Th17 differentiation.…”
Section: Discussionmentioning
confidence: 86%
“…A cysteine in unique sc tail induced disulfide bonding and was more functional in regulation of cytokine signaling than monomer or mc, resulting in effectively outcompeting mc for binding to other c cytokine receptors. Although, in this study, we showed that TCR stimulation upregulates sc expression [11] , further studies will be required to understand what intrinsic factors activate the alternative splicing for sc generation upon TCR stimulation and what extrinsic factors except for TCR stimulation regulates sc expression.…”
Section: Generation Of Scmentioning
confidence: 79%
“…However, what mechanisms are responsible for the production of sc, what are biological functions of sc, and how sc is involved in regulating key inflammatory and immune response have been unclear. Our recent publication demonstrated that sc expression was upregulated upon TCR stimulation and was generated by alternative splicing, which led to only identical extracellular domain to the membrane c with unique short amino acid sequence in the absence of transmembrane and intracellular domain [11] . A cysteine in unique sc tail induced disulfide bonding and was more functional in regulation of cytokine signaling than monomer or mc, resulting in effectively outcompeting mc for binding to other c cytokine receptors.…”
Section: Generation Of Scmentioning
confidence: 99%
See 1 more Smart Citation